Influence of Dynamic Pricing, UI, and UX on Gojek Usage Decisions among Gen Z in Depok - Novitasari, Novitasari; Rachmawati, Dwi; Udriyah, Udriyah (Faculty of Economics and Business, Universitas Klabat, 2026)
The rapid development of digital technology has increased the use of online transportation applications in Indonesia. From 2021 to 2023, Gojek maintained the highest number of downloads, although a significant decline was recorded, while competitors such as Maxim and inDrive experienced growth. This phenomenon highlights the urgency to analyze factors that influence usage decisions, particularly among Generation Z. This study aims to examine the influence of dynamic pricing, user interface (UI), and user experience (UX) on the decision to use the Gojek application among Generation Z in Depok City. A quantitative survey was conducted involving 100 respondents selected through incidental sampling. Data were analyzed using multiple linear regression with IBM SPSS version 27. The findings indicate that: (1) dynamic pricing significantly influences the decision to use Gojek; (2) user interface does not significantly influence usage decisions; (3) user experience is the strongest predictor with a significant influence; and (4) dynamic pricing, UI, and UX jointly have a significant influence on the decision to use Gojek.